Traces behind the Esmeraldas shore : prehistory of the Santiago-Cayapas Region, Ecuador - DeBoer, Warren R. (Tuscaloosa, Ala. : University of Alabama Press, 1996)
"Survey along the lower Cayapas and Santiago rivers located ca. 200 habitation sites. Ceramic distinctions define seven phases, partly sequential and partly regional; 25 C14 dates extend from ca. 400 BC to AD 1400. Settlements become smaller, more dispersed, and culturally isolated after ca. AD 400"--Handbook of Latin American Studies, v. 57
1. Backward -- 2. Coast, River, and Forest -- 3. Sketching the Sequence -- 4. Vagrant Vestiges: Valdivia and the Mafa Phase -- 5. La Tolita's Hinterland: The Selva Alegre Phase -- 6. From Patas to Pedestals: The Guadual Phase -- 7. La Tolita's Aftermath: Herradura, Las Cruces, and Mysterious Mina -- 8. Back to Barbarism: The Tumbaviro Phase -- 9. The Coming of the Chachi -- 10. Local Linkages and Global Extensions -- Appendix 1. Textiles -- Appendix 2. Phytoliths.
Includes bibliographical references (pages 221-229) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Indians of South America -- Ecuador -- Esmeraldas (Province) -- Antiquities; Indians of South America -- Material culture -- Ecuador -- Esmeraldas (Province); Cayapa Indians -- Antiquities; Excavations (Archaeology) -- Ecuador -- Esmeraldas (Province); Esmeraldas (Ecuador : Province) -- Antiquities; HISTORY; Antiquities; Excavations (Archaeology); Indians of South America -- Antiquities; Indians of South America -- Material culture; Ecuador -- Esmeraldas (Province); Archäologie; Vor- und Frühgeschichte; Esmeraldas; Cayapa (Indiens) -- Antiquités.; Indiens -- Équateur -- Esmeraldas (Province) -- Antiquités.; Indiens -- Équateur -- Esmeraldas (Province) -- Culture matérielle.; Fouilles archéologiques -- Équateur -- Esmeraldas (Province); Esmeraldas (Équateur ; province) -- Antiquités.; Antiquities; Ecuador -- History